Etnografi Pembelajaran PAI: Bagaimana Sekolah Alam Mengintegrasikan Sains dan Agama? - Brillian Agree El Islamy; Darmanto Darmanto (Bustanul Ulum Journal of Islamic Education, 2026)
Islamic Religious Education in elementary schools is still frequently taught separately from science education, resulting in students being unable to fully understand the relationship between Islamic values and natural phenomena. This study aims to describe the integration of science into experiential learning Islamic Religious Education, particularly in Islamic elementary schools that adopt a nature school approach. The study employed a qualitative method using a case study design. Data were collected through observations, interviews, and documentation involving the principal, PAI teachers, classroom teachers, and students. Data were analyzed through data reduction, data display, and conclusion drawing. The findings revealed that the integration of science into IRE learning was implemented through the utilization of the natural environment as a learning resource, the observation of natural phenomena, environmental exploration, experiential reflection, and the integration of scientific concepts with Qur’anic verses and Islamic values. Experiential learning encouraged students to engage in active, contextual, and reflective learning processes. In addition to enhancing students’ religious understanding, the learning process also promoted scientific literacy, critical thinking skills, environmental awareness, and spiritual consciousness. These findings indicate that the integration of science into experiential learning-based Islamic Religious Education can serve as a holistic, meaningful, and relevant learning model that addresses the demands of twenty-first-century education.